REQUIREMENTS FOR CREATION AND CONDUCT OF COMPLEXES OF GYMNASTIC EXERCISES AND METHODS FOR THEIR CREATION FOR DIFFERENT PRESCHOOL AGES (Scientific journal of the Fergana State University, 2024)
The article analyzes how the acquisition of gymnastic exercises and other motor skills by preschoolers has a good effect on their physical development, as well as on their health. As well as Morning gymnastics for children, physical exercises, classes in some kind of children's sports, games, roller skating, roller skiing, bicycles  and benefits of walking have found practical expression.